2014
DOI: 10.3390/v6031395
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Targeting HIV Entry

Abstract: Despite the unquestionable success of antiretroviral therapy (ART) in the treatment of HIV infection, the cost, need for daily adherence, and HIV-associated morbidities that persist despite ART all underscore the need to develop a cure for HIV. The cure achieved following an allogeneic hematopoietic stem cell transplant (HSCT) using HIV-resistant cells, and more recently, the report of short-term but sustained, ART-free control of HIV replication following allogeneic HSCT, using HIV susceptible cells, have ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…CCR5 is an ideal target for Studies have indicated that the CCRT antagonist combined with HAART treatment can shrink the latent virus [28] , but whether will it apply to the large sample. that needs further study cannot clear it [29,30] .…”
Section: Ccr5 Antagonist Of Chemokine Receptormentioning
confidence: 98%
“…CCR5 is an ideal target for Studies have indicated that the CCRT antagonist combined with HAART treatment can shrink the latent virus [28] , but whether will it apply to the large sample. that needs further study cannot clear it [29,30] .…”
Section: Ccr5 Antagonist Of Chemokine Receptormentioning
confidence: 98%
“…Although CCR5 is the primary co-receptor for HIV, CXCR4-tropic strains are often found at low levels in chronically infected individuals and advanced stage HIV infection [76,77], and the outgrowth of CXCR4-tropic strains or the evolution of tropism-switching viruses after treatment with CCR5-modified cells is a concern. To address this, gene editing of CXCR4 as an alternative, or in conjunction to, CCR5 has also been explored.…”
Section: Locking Out Hiv: Gene Therapy Strategies That Target Hiv Entrymentioning
confidence: 99%
“…Approaches that modify autologous cells to make them resistant to HIV-1 have been favored [141,247,248]. Gene-based prophylactic or therapeutic immunostimulations are discussed in Chapter 11, and clinical trials aimed at direct HIV-1 treatment are considered here.…”
Section: Clinical Trials Using Gene Therapy To Treat Hiv-1 Infectionmentioning
confidence: 99%